Polyester Film Untuk Kemasan - Zulfa Humam (Balai Besar Kimia dan Kemasan, 1987)
Amongst the wide variety of polymer film lately available, no other film hasrevolutionized the flexible packaging then the polyster film polyester film because of its out standing properties has an unique plase amongst other plastic film. Because of this film provides high effeciency in the processess of printing, lamination, sealing bag making and automatic packaging. It can printed at a higher speed than other plastic films on conventional printing machines.